Firm export dynamics and the exchange rate: A quantitative exploration - Bernabe Lopez-Martin (Banco de México, 2019)
We develop a quantitative theoretical model of firm dynamics to analyze key determinants of the elasticity of exports with respect to the exchange rate. The model incorporates mechanisms that determine the firms? capacity to react when the profitability of exports change due to fluctuations in the exchange rate. The framework allows for a quantitative assessment of different mechanisms: distribution costs represent the most important factor, as well as the exogenous and gradual growth dynamics of new exporters, and the currency denomination of sunk-entry costs into the foreign market. The different versions of the model are evaluated by contrasting the behavior of simulated variables with empirical estimates and evidence found in the literature. In addition, we present an assessment of the effects on the intensive and extensive margins of exports.
Keywords: F12; F41; 330; export dynamics; hysteresis; exchange rates; heterogeneous firms; exchange rate passthrough